"I don't complain, but I am ready for any eventuality": How job search and sportsmanship interact in the prediction of intention to leave a profession. Issue 3 (8th July 2019) - Paillé, Pascal; Valéau, Patrick
Abstract : Purpose: The purpose of this paper is to investigate the extent to which the influence of professional commitment on intention to leave a profession is contingent on the combined effect of job search and sportsmanship. Design/methodology/approach: The research is based on a sample of professional employees ( N = 327). Moderated moderation was the approach used for testing the hypotheses. Findings: Findings showed that the moderating effect of job search on the relationship between professional commitment and intention to leave a profession is higher at a low level of sportsmanship and lower when sportsmanship is high. Originality/value: The research indicates that job search does not necessarily constitute a sign of acceleration of intention to leave one's profession. In the case of professionals expressing a high level of sportsmanship, job search appears more like a precaution.